1999
DOI: 10.1038/sj.bjc.6690186
|View full text |Cite
|
Sign up to set email alerts
|

Motility-related protein (MRP-1/CD9) and KAI1/CD82 expression inversely correlate with lymph node metastasis in oesophageal squamous cell carcinoma

Abstract: Metastasis of cancer cells is believed to be influenced by many factors which progress through several stages as cancer cells move from a primary lesion to metastatic sites. One of those factors, cell motility, plays an important role in the progression, especially after the extravasation. Motility-related protein 1 (MRP-1/CD9), which belongs to the transmembrane 4 superfamily of membrane proteins, is considered to inhibit cell motility (Miyake et al, 1991). It has been demonstrated that the cells which expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 12 publications
7
66
1
Order By: Relevance
“…Moreover, we revealed that reduced MRP-1/CD9 expression was associated with a poor prognosis in patients with breast cancers, non-small cell lung cancers (NSCLC) and pancreatic cancers (Miyake et al, 1996;Higashiyama et al, 1995;Sho et al, 1998). In addition, other laboratories reported the same phenomenon in colon cancer and esophageal cancer (Mori et al, 1998;Uchida et al, 1999). Thus, this gene suppresses tumor metastasis in various cancers, and its decreased expression may be involved in malignant progression.…”
Section: Introductionsupporting
confidence: 53%
“…Moreover, we revealed that reduced MRP-1/CD9 expression was associated with a poor prognosis in patients with breast cancers, non-small cell lung cancers (NSCLC) and pancreatic cancers (Miyake et al, 1996;Higashiyama et al, 1995;Sho et al, 1998). In addition, other laboratories reported the same phenomenon in colon cancer and esophageal cancer (Mori et al, 1998;Uchida et al, 1999). Thus, this gene suppresses tumor metastasis in various cancers, and its decreased expression may be involved in malignant progression.…”
Section: Introductionsupporting
confidence: 53%
“…5,7,10,34 The involvement of the CD9 molecule in metastasis has been further inferred from the inhibition of tumor cell motility and migration caused by CD9 specific mAbs or by overexpression of this tetraspanin. 5,7,9,10 While this implication of CD9 in metastasis has been documented in numerous studies and is fairly well established, much less attention has been however devoted to the possi- ble involvement of this tetraspanin in the early stages of tumor formation, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In order to define the location of the plasma membrane more clearly, the cells were treated with an antibody against the CD-9 protein, that is located on the plasma membrane in a number of cell types. 24,33 Immunofluorescence images of LNCaP cells treated with the anti-CD-9 antibody revealed a clear location of the CD-9 protein at the plasma membrane of cells transfected with pCMV-EGFP-TRPL (Fig 3b) and cells transfected with pCMV-EGFP-C1 (Fig 3e). Overlay of the CD-9 and EGFP-TRPL images for each cell transfected with pCMV-EGFP-TRPL showed that the EGFP-TRPL chimeric protein and the CD-9 protein are colocated at the plasma membrane in a band (about 30-50% of the plasma membrane) of the cell (Fig 3c, indicated by the orange color (arrows)).…”
Section: Expression Of the Trpl Protein In Transiently Transfected Lnmentioning
confidence: 99%